2022
DOI: 10.3389/fnins.2022.1029327
|View full text |Cite
|
Sign up to set email alerts
|

Cervical alignment and clinical outcome of anterior decompression with fusion vs. posterior decompression with fixation in kyphotic cervical spondylotic myelopathy

Abstract: Background contextCervical kyphosis is a common but potentially debilitating and challenging condition. There is controversy on the optimal surgical strategy for the treatment of kyphotic cervical spondylotic myelopathy (KCSM) using either anterior approach or posterior approach.IntroductionThe purpose of this study was to investigate the surgical efficacy of anterior decompression with fusion (ADF) vs. posterior decompression with fixation (PDF) for the treatment of KCSM, and to further analyze the changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Fifteen studies that showed the relationship between cervical alignment and outcome following posterior fusion are listed in Table 3 [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 116 ]. We summarize the pre- and postoperative risk factors for each parameter and other etiologies in the cervical spine in Table 3 .…”
Section: Selection Of Surgical Techniques For Dcm and Cervical Spine ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies that showed the relationship between cervical alignment and outcome following posterior fusion are listed in Table 3 [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 116 ]. We summarize the pre- and postoperative risk factors for each parameter and other etiologies in the cervical spine in Table 3 .…”
Section: Selection Of Surgical Techniques For Dcm and Cervical Spine ...mentioning
confidence: 99%
“…Satisfactory neurological improvement was obtained with all of the surgical types. However, ADF was more suitable than P-F in restricting postoperative kyphotic change and an increase in SVA, even if ADF was not suitable for more than three levels of spinal cord compression [ 101 ]. Another article revealed that the most important cervical sagittal parameters correlating with clinical outcomes were C7 slope, occipito-C2 angle, external auditory meatus tilt, and SVA and that ADF more efficiently restored cervical sagittal alignment [ 102 ].…”
Section: Selection Of Surgical Techniques For Dcm and Cervical Spine ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical spondylotic myelopathy (CSM) is a chronic degenerative disorder, which often involve the spinal cord compression or ischemia, producing a gradual decrease in neurological function and patient's quality of life. On X-rays, patients with CSM often show cervical local kyphosis (CLK) due to the intervertebral height decrease and sagittal lordotic malalignment, as well as the discs and facet joints degeneration [ 1 ]. Major symptoms include neck fatigue, neck pain, myelopathy, radiculopathy, horizontal gaze problems, and swallowing and breathing abnormalities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%